Analisis Pengaruh Pemasaran Digital dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Usaha Mikro Kecil Dan Menengah (UMKM) di Kota Bengkulu. - Azuwandri, Azuwandri; Mulyadi, Mulyadi; Akmal, Samsul; Fhikri, Rijalul; Yuningsih, Siti (Jurnal Administrasi Bisnis Nusantara, 2026)
The development of digital technology has transformed the way businesses, including Micro, Small, and Medium Enterprises (MSMEs), market their products. This study aims to analyze the effect of digital marketing and product quality on customer satisfaction in MSMEs in Bengkulu City. Customer satisfaction plays a vital role in ensuring business sustainability, especially for MSMEs that must compete in a dynamic and competitive market environment.This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 91 respondents who were customers of various MSMEs in Bengkulu City. The data were analyzed using multiple linear regression to examine the simultaneous and partial effects of the independent variables (digital marketing and product quality) on the dependent variable (customer satisfaction). Validity and reliability tests, as well as classical assumption tests, were conducted to ensure the accuracy and suitability of the research instruments and model.The results of the study indicate that both digital marketing and product quality have a positive and significant effect on customer satisfaction. Partially, product quality shows a more dominant influence compared to digital marketing.